PERANAN MANAJEMEN SUMBER DAYA MANUSIA PADA UMKM SEBLAK PRASMANAN BUNDA REZKY DI KABUPATEN SUBANG: Studi Kasus UMKM Kuliner di Kabupaten Subang - Mutqi Sopiawadi; Amelia Julianti; Rista Herlina; Usi Komalasari (Gapura (Garba Pembangunan Masyarakat), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in the regional economy, particularly in employment absorption. The success of MSMEs is not only determined by product quality but also by effective human resource management (HRM). This study aims to analyze the role of HRM in Seblak Bunda Rezky Buffet MSMEs in Subang Regency, focusing on production competence, marketing competence, and entrepreneurial competence. This research uses a descriptive qualitative approach through observation and interviews with the business owner. The results show that production competence is relatively good, although it is constrained by workforce flexibility and per-portion cooking processes. Marketing competence has not been optimal due to the absence of dedicated marketing personnel, while the owner’s entrepreneurial competence is considered good. This study concludes that strengthening HRM, especially in marketing and operational systems, is necessary to improve competitiveness and business sustainability.